Handbook of food toxicology - Deshpande, S. S. (Marcel Dekker, 2002)
This text explores toxin sources, mechanisms, routes of exposure and absorption, and their chemical and biological components to prevent contamination of food products and reduce epidemics of foodborne disease.
Keywords: Food -- Toxicology -- Handbooks, manuals, etc.; elektronické knihy; electronic books